Short Communication: Species diversity of corticolous lichens in the arboretum of Padjadjaran University, Jatinangor, Indonesia - JOKO KUSMORO; BETTY MAYAWATIE; RULLY BUDIONO; IIN SUPARTINAH NOER; RIRIN EKA PERMATASARI; ALISA NURWAHIDAH; RIKA SATRIAWATI; DIAH ARUM; DORA ERAWATI SARAGIH; RIA WIDYA; MUHAMAD FEISAL JATNIKA; AFIF MAKARIM; RUHYAT PARTASASMITA (Society for Indonesian Biodiversity, 2019)
Abstract. Kusmoro J, Mayawatie B, Budiono R, Noer IS, Permatasari RE, Nurwahidah A, Satriawati R, Arum D, Saragih DE, Widya R, Jatnika MF, Makarim A, Partasasmita R. 2019. Short Communication: Species diversity of corticolous lichens in the arboretum of Padjadjaran University, Jatinangor, Indonesia. Biodiversitas 20: 1606-1616. The lichen flora of tropical areas is still much under explored, Java in general and the Arboretum in West Java in particular, are no exceptions. The Arboretum of the main campus of Padjadjaran University, Jatinangor, Sumedang, West Java, Indonesia is representative of a typical man-made lowland tropical rain forest ecosystem in Java. It is planted with peculiar and rare species of plants, such as Antidesma bunius, Syzygium cumini, Durio zibethinus, Caesalpinia pulcherrima, Tectona grandis, Albizzia falcataria, Swietenia mahagoni, Alstonia scholaris, Jatropha multifida, Sterculia foetida, Diospyrus blancoi, Hura crepitans and Rauvolfia serpentina. We explored the lichen flora of this Arboretum using species of corticolous macrolichens as indicator taxa. Lichen survey was performed by exploring the different zones, such as zones for rare species, industrial plants, medicinal plants and fruit plants. Lichen diversity on 23 trees spread in 12 ha area was documented based on morphological and anatomical features, and also chemical tests. A total of 68 species of lichens, distributed in 38 genera and 12 families, were enumerated during the study. The crustose and foliose forms contributed 62% (42 species) and 37% (25 species) of the total species, respectively. Graphidaceae with 28 species and Parmeliaceae with 15 species were the dominant families, which together constituted more than 50% of the lichen populations. Graphis librata and Parmeliopsis sp. were the dominant and co-dominant species and Drinaria picta was another common species.